Ectodysplasin A regulates epithelial barrier function through sonic hedgehog signalling pathway. Issue 1 (7th August 2017) - Li, Sanming; Zhou, Jing; Zhang, Liying; Li, Juan; Yu, Jingwen; Ning, Ke; Qu, Yangluowa; He, Hui; Chen, Yongxiong; Reinach, Peter S.; Liu, Chia‐Yang; Liu, Zuguo; et al.
Abstract: Ectodysplasin A (Eda), a member of the tumour necrosis factor superfamily, plays an important role in ectodermal organ development. An EDA mutation underlies the most common of ectodermal dysplasias, that is X‐linked hypohidrotic ectodermal dysplasia (XLHED) in humans. Even though it lacks a developmental function, the role of Eda during the postnatal stage remains elusive. In this study, we found tight junctional proteins ZO‐1 and claudin‐1 expression is largely reduced in epidermal, corneal and lung epithelia in Eda mutant Tabby mice at different postnatal ages. These declines are associated with tail ulceration, corneal pannus formation and lung infection. Furthermore, topical application of recombinant Eda protein markedly mitigated corneal barrier dysfunction. Using cultures of a human corneal epithelial cell line and Tabby mouse skin tissue explants, Eda up‐regulated expression of ZO‐1 and claudin‐1 through activation of the sonic hedgehog signalling pathway. We conclude that EDA gene expression contributes to the maintenance of epithelial barrier function. Such insight may help efforts to identify novel strategies for improving management of XLHED disease manifestations in a clinical setting.